The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1590/1678-7757-2017-0112
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chlorhexidine preprocedural rinse on bacteremia in periodontal patients: a randomized clinical trial

Abstract: Objective:Single dose of systemic antibiotics and short-term use of mouthwashes reduce bacteremia. However, the effects of a single dose of preprocedural rinse are still controversial. This study evaluated, in periodontally diseased patients, the effects of a pre-procedural mouth rinse on induced bacteremia.Material and Methods:Systemically healthy individuals with gingivitis (n=27) or periodontitis (n = 27) were randomly allocated through a sealed envelope system to: 0.12% chlorhexidine pre-procedural rinse (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 28 publications
(54 reference statements)
0
26
0
Order By: Relevance
“…The risk of bacteremia has been associated with periodontal health status in a systematic review, suggesting a higher risk of bacteremia associated with gingival inflammation (Tomas, Diz, Tobias, Scully, & Donos, ). A recent randomized clinical trial (RCT) concluded that periodontal therapy (by means of scaling and root planing, SRP) induced bacteremia in both gingivitis and periodontitis patients, but the magnitude and frequency were greater among periodontitis patients (Balejo et al, ).…”
Section: Mechanisms That May Explain the Epidemiological Associationsmentioning
confidence: 99%
“…The risk of bacteremia has been associated with periodontal health status in a systematic review, suggesting a higher risk of bacteremia associated with gingival inflammation (Tomas, Diz, Tobias, Scully, & Donos, ). A recent randomized clinical trial (RCT) concluded that periodontal therapy (by means of scaling and root planing, SRP) induced bacteremia in both gingivitis and periodontitis patients, but the magnitude and frequency were greater among periodontitis patients (Balejo et al, ).…”
Section: Mechanisms That May Explain the Epidemiological Associationsmentioning
confidence: 99%
“…The risk of bacteremia has been associated with periodontal health status in a systematic review, suggesting a higher risk of bacteremia associated with gingival inflammation [127]. A recent randomized clinical trial (RCT) concluded that periodontal therapy (by means of scaling and root planing, SRP) induced bacteremia in both gingivitis and periodontitis patients, but the magnitude and frequency were greater among periodontitis patients [5].…”
Section: Is There Evidence Of a Higher Incidence Of Bacteremia Followmentioning
confidence: 99%
“…9 Most studies on oral bacterial focused on the number of different species of bacteria present in the oral cavity or tooth surfaces the general report is that the number of oral bacteria is higher in neglected/dirty mouth as well as patients with increased pathogenicity of oral bacterial due to impaired immunity and those with increased plaque and calculus accumulation. [10][11][12] This study, aimed at determining the salivary bacterial count in apparently healthy individuals, showed that the mean bacterial count of apparently healthy Nigerian was 8.41 × 108 + 1.06 × 10 9 per mL of saliva. A progressively increasing salivary bacterial count progressively was also observed as oral hygiene tends towards becoming poor.…”
Section: Discussionmentioning
confidence: 98%